On-farm management of applied inputs and native soil fertility (IRRI, 1998)
Contents: Introduction to the mega project on reviewing trends of declinning productivity in intensive irrigated rice systems; biophysical reports from the national sites; socioeconomic reports from the national sites; cross-site reports from IRRI staff.